Pengembangan Blended Learning Tipe Station Rotation Model Berbasis Project Based Learning Berorientasi Kemampuan Berpikir Kritis Matematis Siswa SMP - Amelya Permata Sari; Jefri Marzal; Zurweni Zurweni (Journal on Education, 2025)
This research aims to determine the development of a station revolution type blended learning model based on project based learning focused on junior high school students' mathematical critical thinking abilities consisting of a station rotation type blended learning learning method, a project based learning learning model, and a focus on students' critical thinking. This research is development research using the ADDIE method with development stages of individual trials, small group trials and field trials. This research was carried out at SMP N 5 Jambi City in class VIII.G, the instruments used were open and closed questionnaires as well as pretest and posttest questions, this research data was qualitative and quantitative using the N-gain test. The results of this research obtained a value of 0.7748, which can be classified as an increase in the N-Gain score, the ability to develop Blended learning based on the PjBL model, critical thinking orientation is categorized as high, and the results of the pre-test and post-test are critical thinking oriented for 39 students after learning. dare to use the PjBL RPP model in a BL type Station rotation material, straight line equations, the percentage of N-gain values ​​obtained in the pretest and posttest analysis of the mathematical critical thinking questionnaire is 77.48%. interpret the increase in effective mathematical critical thinking skills.